2014
DOI: 10.5194/bg-11-5931-2014
|View full text |Cite
|
Sign up to set email alerts
|

Pigments, elemental composition (C, N, P, and Si), and stoichiometry of particulate matter in the naturally iron fertilized region of Kerguelen in the Southern Ocean

Abstract: Abstract. The particulate matter distribution and phytoplankton community structure of the iron-fertilized Kerguelen region were investigated in early austral spring (October-November 2011) during the KEOPS2 cruise. The iron-fertilized region was characterized by a complex mesoscale circulation resulting in a patchy distribution of particulate matter. Integrated concentrations over 200 m ranged from 72.2 to 317.7 mg m −2 for chlorophyll a 314 to 744 mmol m −2 for biogenic silica (BSi), 1106 to 2268 mmol m −2 f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
86
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(102 citation statements)
references
References 107 publications
(173 reference statements)
16
86
0
Order By: Relevance
“…It should be borne in mind that this does not constitute a typical model validation, but a partial and indirect verification of our model. For instance, the seasonal evolution of silicate is not only controlled by the abundance of diatoms but also by their level of silicification (their Si:C ratio), which can be highly variable (Lasbleiz et al, 2014;Martin-J ez equel et al, 2000;Sarthou et al, 2005) depending on the growing conditions this group experiences (Brzezinski, 1985;Bucciarelli et al, 2010;Hoffmann et al, 2007;Lasbleiz et al, 2014). We find that the seasonal evolution of surface silicate concentrations (Si) in the PHYSIO experiment is Journal of Geophysical Research: Oceans 10.1029/2018JC013775 improved when compared to climatological data in two hydrological provinces (Figures 11a and 11b).…”
Section: Is the Change In The Diatoms Contribution To Total Primary Pmentioning
confidence: 99%
“…It should be borne in mind that this does not constitute a typical model validation, but a partial and indirect verification of our model. For instance, the seasonal evolution of silicate is not only controlled by the abundance of diatoms but also by their level of silicification (their Si:C ratio), which can be highly variable (Lasbleiz et al, 2014;Martin-J ez equel et al, 2000;Sarthou et al, 2005) depending on the growing conditions this group experiences (Brzezinski, 1985;Bucciarelli et al, 2010;Hoffmann et al, 2007;Lasbleiz et al, 2014). We find that the seasonal evolution of surface silicate concentrations (Si) in the PHYSIO experiment is Journal of Geophysical Research: Oceans 10.1029/2018JC013775 improved when compared to climatological data in two hydrological provinces (Figures 11a and 11b).…”
Section: Is the Change In The Diatoms Contribution To Total Primary Pmentioning
confidence: 99%
“…It was hypothesized that the addition of silicic acid promoted the growth of diatoms, which increased export of POC (Engel et al, 2002;Kemp et al, 2006;Kemp and Villareal, 2013;Rynearson et al, 2013;Lasbleiz et al, 2014). However, later studies showed that artificial mixing of upper water layers also initiated aggregate formation even in the absence of diatoms, suggesting that diatoms (and indirectly silicic acid) were not the sole trigger of high POC fluxes (Svensen et al, 2001(Svensen et al, , 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Satellite images of surface chlorophyll concentrations show that the Kerguelen plume is highly heterogeneous, displaying strong gradients even within the plume itself, in response to eddies and frontal structures (Figure 1c)). The community structure of the bloom's primary producers has been studied during ship-based oceanographic campaigns, which have focused mainly on differentiating diatoms types and on pigment and size analyses Lasbleiz et al, 2014Lasbleiz et al, , 2016Mosseri et al, 2008;Qu eguiner, 2013;Trull et al, 2015;Uitz et al, 2009). However, in-situ observations are limited in spatial extent by the large size of the plume and the remoteness of the area.…”
Section: Overview Of the Study Regionmentioning
confidence: 99%